SWOT Matrix Analysis of Gastronomic Features of Fermented Products in Cisambeng Village, Majalengka - Dewi Turgarini; Astri Inas Yuthika; Armandha Redo Pratama (Universitas Pendidikan Indonesia, 2023)
This study aims to formulate a digital marketing strategy for fermented products as superior gastronomy in Cisambeng Village, Majalengka Regency. This study uses qualitative research methods with data collection techniques through in-depth interviews, literature studies and documentation studies. The SWOT analysis carried out provides information that fermented food in Majalengka Regency has a great opportunity to be developed into a new food innovation that can build villages in opening job vacancies. SWOT matrix results show that producer of fermented food such as tofu, tempeh, oncom, and dage are experiencing growth, therefore a strength-opportunity strategy can be implemented. This can be achieved by improving the quality of human resources through the recruitment of individuals who are focused on online marketing. Content can be created in the form of videos about the products. The quality of product packaging can be improved to ensure longevity, potentially through the use of vacuum sealing or attractively designed food packages. Existing advertising services owned by social media platforms (online-ads) can be utilized. Consumer reviews can be uploaded on social media to enhance marketing efforts.